How prosthetic design influences knee kinematics: a narrative review of tibiofemoral kinematics of healthy and joint-replaced knees. (1st February 2019) - Meng, Fanhe; Jaeger, Sebastian; Sonntag, Robert; Schroeder, Stefan; Smith-Romanski, Sydney; Kretzer, J. Philippe
ABSTRACT: Introduction : To improve the total knee arthroplasty (TKA) prosthesis design, it is essential to study the kinematics of the tibiofemoral joint. Many studies have been conducted in this area; however, conflicting results and incomparable testing methods make it difficult to draw definitive conclusions or compare research from studies. The goal of this article is to introduce what is known about both healthy and prosthetic tibiofemoral joint kinematics. Areas covered : Healthy tibiofemoral joint kinematics are reviewed in vivo by different activities, and the kinematics of existing knee prosthetic design features are considered separately. These features include but are not limited to cruciate retaining, posterior cruciate substituting, mobile-bearing, and high flexion. Expert commentary : The type of activity that is being performed has a great influence on the kinematics of healthy knees, and the influences of different TKA prosthetic design features on the kinematics are complex and varied. Moreover, the TKA postoperative functional performance is influenced by many factors, and prosthetic design is among them, but not the only one that defines the performance.